Sacred Law in Secular Systems: Shariawiz and Digital Inheritance Fiqh among Muslim Minorities in the United States - Nurulita, Fitri; Melikiati, Neilta; Al Farisi, Maulana Achsan; Alvian, Muhamad (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2025)
For Muslim minorities living within secular legal frameworks, the requirement to comply with Islamic inheritance law (farā’iḍ), while simultaneously upholding the principle of individual freedom, constitutes a persistent legal and religious challenge. This study investigates how digital innovation, exemplified by the Shariawiz digital platform, addresses this tension by facilitating the application of Islamic inheritance principles within the parameters of United States estate law. Employing a qualitative juridical-normative methodology, the research examines the integration of classical Islamic inheritance doctrines into legally recognized instruments such as wills and trusts. Drawing upon the four Sunni madhhabs (Hanafi, Maliki, Shafi‘i, and Hanbali) and situated within the fiqh of Muslim minorities (fiqh al-aqalliyyāt), the study evaluates the adaptability of farā’iḍ principles in minority contexts. The findings indicate that, notwithstanding interpretive variations, Islamic inheritance law consistently prioritizes proportional justice, kinship protection, and social equilibrium. Shariawiz implements these principles by integrating mandatory Islamic norms with the adaptable framework of United States estate law, utilizing scholar-certified digital computations and legally compliant documentation. This study advances the emerging scholarship on Islamic studies in the digital era by demonstrating how technologically mediated ijtihād facilitates the operation of Islamic law within pluralistic legal frameworks. Furthermore, it emphasizes the imperative for comparative research across different jurisdictions.